Variação lexical em Abaetetuba-PA - CARDOSO, Ellen Susy Macedo (2019)
In this present paper, it looks for approach the lexical variation in the city of Abaetetuba, State of Para. It has as orientation theoretical-methodological the variationist sociolinguistic and the linguistic geography, since analyze both questions of social nature and dialectal. From the application of the questionnaire semantic – lexical (QSL), done and used by the project Linguistic Atlas of Brazil (ALiB), there are six men, with different ages, born in Abaetetuba, living in three different neighborhoods equidistant in the topography of the county, it was understood the linguistic variation in the city with basis in 5 (five) lexical items, for which were thought 5 (five) lexical letters. It was observed that there is a relative difference between the terms, especially in what refers to social specificities of the informants. This way, young individuals seems to present a lexicon more diversified than older people. By the way, the diatopic variation was noticeable, safe the peculiarities of the way of Abaetetubense speak. Especially in the field of terms related to the religiosity.